Does Prenatal Exposure to CNS Stimulants Increase the Risk of Cardiovascular Disease in Adult Offspring? - Rorabaugh, Boyd R. (Frontiers in Cardiovascular Medicine, 2021)
Prenatal exposure to an adverse uterine environment can have long lasting effects on adult offspring through DNA methylation, histone acetylation, and other epigenetic effects that alter gene expression and physiology. It is well known that consumption of CNS stimulants such as caffeine, nicotine, amphetamines, and cocaine during pregnancy can adversely impact the offspring. However, most work in this area has focused on neurological and behavioral outcomes and has been limited to assessments in young offspring. The impact of prenatal exposure to these agents on the adult cardiovascular system has received relatively little attention. Evidence from both animal and human studies indicate that exposure to CNS stimulants during the gestational period can negatively impact the adult heart and vasculature, potentially leading to cardiovascular diseases later in life. This review discusses our current understanding of the impact of prenatal exposure to cocaine, methamphetamine, nicotine, and caffeine on the adult cardiovascular system.